2021
DOI: 10.3390/biomedicines9020128
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Calcium Sulfate Dihydrate into a Mesoporous Calcium Silicate/Poly-ε-Caprolactone Scaffold to Regulate the Release of Bone Morphogenetic Protein-2 and Accelerate Bone Regeneration

Abstract: Tissue engineering and scaffolds play an important role in tissue regeneration by supporting cell adhesion, proliferation, and differentiation. The design of a scaffold is critical in determining its feasibility, and it is critical to note that each tissue is unique in terms of its morphology and composition. However, calcium-silicate-based scaffolds are undegradable, which severely limits their application in bone regeneration. In this study, we developed a biodegradable mesoporous calcium silicate (MS)/calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…MSCS ceramic composites were fabricated according to our previous study [ 20 ]. Firstly, 3.3 g cetyltrimethylammonium bromide (CTAB, Sigma-Aldrich, St. Louis, MO, USA) was blended with 6 mL NH 3 ·H 2 O in distilled water (ddH 2 O, 300 mL) and stirred for 15 min at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCS ceramic composites were fabricated according to our previous study [ 20 ]. Firstly, 3.3 g cetyltrimethylammonium bromide (CTAB, Sigma-Aldrich, St. Louis, MO, USA) was blended with 6 mL NH 3 ·H 2 O in distilled water (ddH 2 O, 300 mL) and stirred for 15 min at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Si can also support adhesion interactions between cells and scaffolds, as well as promote angiogenesis-related functions of human umbilical vein endothelial cells [ 19 ]. Our previous studies have shown that mesoporous calcium silicate/calcium sulfate scaffold (MSCS) could provide a favorable microenvironment for cell proliferation, differentiation, and bone mineralization [ 20 ]. In addition, MSCS scaffolds showed anti-bacterial effects and had enhanced mechanical properties, which were able to support long-term drug release and enhanced bone regeneration in animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are considered to be the most eminent in advancing bone growth by inducing osteogenic differentiation [ 1 , 6 , 15 ]. In Jang’s study [ 106 ], they made alginate/BMP-2/umbilical cord serum (UCS) coated on 3D-printed PCL scaffolds and demonstrated that the simultaneous use of low-dose BMP-2 and UCS significantly increased osteogenesis based in vitro and in vivo.…”
Section: Pcl-based Composite 3d Scaffoldsmentioning
confidence: 99%
“…Autogenous bone transplantation and replacement are the main traditional options for patients with bone defects [ 3 , 4 ]. However, the potential risks of tissue grafts including complications and secondary injuries remain a major clinical challenge [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of calcium sulfate bone substitutes is its fast resorption, which exceeds the bone formation/growth rate at the defect site, leading to the creation of pores after its degradation [ 14 , 15 , 16 ]. Furthermore, despite the bone regeneration property of CS bone cements, they need to be combined with another tougher material to achieve enhanced mechanical performance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%